On languages on islands. Issue 1 (2nd January 2020) - Nash, Joshua; Bakker, Peter; Bøegh, Kristoffer Friis; Daval-Markussen, Aymeric; Haberland, Hartmut; Kedwards, Dale; Ladhams, John; Levisen, Carsten; Markússon, Jón Símon; Robbe, Joost; Willemsen, Jeroen
ABSTRACT: Islands as specific research sites in their own right have been given little direct attention by linguists. The physical segregation, distinctness, and isolation of islands from mainland and continental environments may provide scholars of language with distinct and robust sets of singular and combined case studies for examining the role of islandness in any appreciation of language. Whether distinct and particular sociolinguistic and typological phenomena can be attributable to islands and their islandness and vice versa remains unexplored. This position article considers the possibility of there being anything particular and peculiar about languages spoken on islands as compared to languages spoken on mainlands and continents. It arose out of a workshop titled 'Exploring island languages' held at Aarhus University, Denmark on 30 April 2018. The main question posed was: Is there anything special socially, linguistically, grammatically, and typologically about the languages of islands? If so, is it possible to talk about such a thing as an island language?